CLASSIFICATION OF INFORMATION FLOWS IN THE TOURISM BUSINESS (INNOVATIVE ECONOMY, 2022)
Oleshchuk V.T. CLASSIFICATION OF INFORMATION FLOWS IN THE TOURISM BUSINESSPurpose. The aim of the article is formulation of the main classification features of information flows in the tourism business.Methodology of research. Realization of the established goal of the research involves the use of a certain methodology. To highlight the main approaches, signs and types of information flows, the deduction method was used, which involved the selection of individual structural components based on an in-depth analysis of the characteristics of the phenomenon under study. The classification of signs was carried out on the basis of the method of data systematization. The assessment of the conformity of the positions of the authors with the content of a certain scientific approach was carried out on the basis of the application of a comparative analysis of the content of the provisions of their research.Findings. The main approaches and corresponding classification features of information flows in the tourism sphere are singled out, which made it possible to formulate a typology of the latter. The presented classification of signs and types of information flows was developed taking into account the modern characteristics and specifics of the development of the tourist business, which functions taking into account social transformations, social and economic, information and communication changes.It has been proven that the reference to the given classification signs (multi-branch signs, advertising subject-object sign, marketing-market subject-object sign, sign of synthesized influence) will enable tourism enterprises to make important management decisions in various areas, to carry out analysis and forecasting of future development prospects. It is noted that it cannot be claimed that the presented list of classification features and types of information flows in the tourism sphere is unchanged or is distinguished by stable characteristics for the long term, since the dynamism of the environment can provide transformations in its development.Originality. The classification of signs of information flows in the tourism business has gained further development, in particular, the author put forward and substantiated the sign of synthesized influence, and the main types of information flows in tourism characteristic of it have also been highlighted.Practical value. The given classification of information flows can be used to assess the actual and forecast types and characteristics of information flows in the tourism business.Key words: information flows, tourism business, synthesized impact, multi-industry features, advertising subject-object feature, marketing-market subject-object feature, advantages, negative impact.
Keywords: information flows; tourism business; synthesized impact; multi-industry features; advertising subject-object feature; marketing-market subject-object feature; advantages; negative impact